Extent of Farm Mechanization in North Bank Plains Zone of Assam, India - Alam, Suhail; Sharma, Haridra; Saharia, Ridip Ranjan; Sonowal, Arunjyoti; Baruah, Amvrin (International Journal of Economic Plants, 2025)
The study was conducted from April, 2022 to March, 2023 in the North Bank Plains Zone (NBPZ) of Assam, India to assess the extent of mechanization and its impact on crop production. Among the six (6) districts of North Bank Plains Zone of Assam, three districts viz., Lakhimpur, Sonitpur and Darrang were selected randomly. Mechanization Index (MI) values were calculated for three key crops: sali rice, toria, and potato. Among these, potato had the highest MI (84.87%), followed by sali rice (74.65%) and toria (51.29%). Most farmers (72%) were classified under the medium mechanization category, indicating a moderate adoption of agricultural machinery. Mechanization significantly improved cropping intensity, which rose from 131.42% to 140.93%, an 8.45% increase, highlighting more effective land utilization and higher productivity. Additionally, mechanization reduced labor intensity, increased operational efficiency, and enhanced yields across crops. However, the adoption of mechanized technologies was not without challenges. Farmers faced high fuel costs, inadequate access to machinery during peak agricultural seasons, and a shortage of skilled personnel for machine operation and maintenance. Furthermore, frequent machinery breakdowns, often attributed to poor quality, disrupted farming activities and escalated costs. To address these challenges, the establishment of additional custom hiring centers (CHCs) was recommended. These centers would enable farmers to access high-quality machinery at affordable rates, minimizing delays and operational costs. Furthermore, training programs for operators and regular maintenance support at CHCs could alleviate technical difficulties. By addressing these constraints, mechanization can be effectively scaled, ensuring increased productivity and fostering sustainable agricultural development in the NBPZ.